De l’indemnisation des dommages matériels : le non-assuré, problématique et prospective - Bélanger, François; Simard Jr., François-Xavier (Assurances, 1982)
In their article, Messrs. François Bélanger and François-Xavier Simard ask themselves the following two questions: 1. Given the application of Article 116 of the Automobile Insurance Act (Québec), is the Uninsured, following an automobile accident, deprived of all avenues of appeal against the liable third party? 2. Is the Liability Insurer entitled to request a subrogation appeal after having compensated the client? Two aspects of the new clauses contained in the Automobile Insurance Act have brought about a rather marked change in market habits. The reader will be struck by the manner in which the co-authors have approached the subject as well as the frankness and genuineness reflected in their article. Their study has enabled them to draw the following conclusion: “Regardless of what we may be able to assert with respect to the Automobile Insurance Act, we must always bear in mind that we are dealing with an Act which, from various points of view, is comprised of a number of original elements. Therefore, the fact that Courts will continue to render contradictory rulings should not surprise us for it will be some time before a consistent and coherent jurisprudence can be established.”